3-D monitoring of rubble mound breakwater damages. (March 2018) - Musumeci, Rosaria E.; Moltisanti, Davide; Foti, Enrico; Battiato, Sebastiano; Farinella, Giovanni M.
Abstract: Breakwaters play a crucial role in the protection of coastal zones. Their maintenance is critical to safeguard the daily activities of harbours and marine areas. The evaluation of damage is a necessity for timely preservation works. Traditional monitoring methods span various techniques, ranging from mechanical profilers to optical systems. Current methods though are expensive, requiring remarkably sophisticated technologies which demand a high degree of expertise to be operated. In this paper, we propose an affordable yet accurate fully automated method based on 3D cameras. Our technique is non invasive, allowing hence non intrusive as well as fast measure of damage over time, simultaneously above and below sea water level. Experimental results obtained on laboratory breakwater models demonstrated that the proposed point cloud method, which does not depend on the imaging sensor and can be applied to any 3D dataset of rubble mound breakwater, can achieve accurate damage estimation, even when using a budget RGB-D camera. One of the additional advantages of using RGB-D cameras is the possibility to obtain measurements also in the presence of water.